Pengaruh Kapitalisasi Pasar Terhadap Pengungkapan Informasi Grafik Key Financial Variable Pada BUMN Di Indonesia - Khairunnisa; Feby Astrid Kesaulya; Weny Putri (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
This study aims to prove that there is an effect of market capitalization on the disclosure of key financial variable graph information. The key financial variable graph in this study is proxied by the EPS chart. This research was conducted in Indonesia using a sample of data from 20 BUMN listed on the Indonesia Stock Exchange during 2017-2019. The results of this study show different results from the indications of previous studies. The results of this study indicate that market capitalization has no positive effect on the disclosure of key financial variable chart information. The greater the market capitalization does not increase the decision of BUMN in Indonesia to disclose the key financial variable graph in their annual report.